Transmigrant Students’ Motivation and Problems in Learning Local Languages: Language Maintenance - Tambunsaribu, Gunawan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Some transmigrant students in their interactions with others have desires to get to know other local languages for various reasons including the student's desire to get to know people who speak the local language more intimately. This study aims to find out the motivations or factors that cause transmigrant students to learn other local languages and what obstacles they face when learning these other local languages. The benefits of this research are to find out the factors the students have and the problems the students encounter in learning local languages as a part of language maintenance. This study used the descriptive qualitative method. The selection of respondents was carried out using the snow bowling technique. There were 50 respondents (transmigrant students) who were living in the dormitory of Universitas Kristen Indonesia, Jakarta. The researcher collected data using questionnaires. The researcher used thematic analysis to analyze the data. This research reveals that there are four main reasons for the students to learn the local language, namely a) because they want to increase their knowledge and skills in the local languages; b) because they want to understand the language and culture of friends from other tribes; c) because they like the local languages (the accent, expression, and intonation); and d) because they want to get closer with fellow students who use the local languages. This study found that there were two types of general barriers that transmigrant students experienced when learning local languages, namely external and internal barriers. This research finds that transmigrant students who live in UKI’s dormitory can be ambassadors of various Indonesian local language maintenance.